Bulk preparation of free‐standing single‐iron‐atom catalysts directly as the air electrodes for high‐performance zinc‐air batteries - Zhang, Hong‐Bo; Meng, Yu; Zhong, Hong; Zhang, Lili; Ding, Shichao; Fang, Lingzhe; Li, Tao; Mei, Yi; Hou, Peng‐Xiang; Liu, Chang; Beckman, Scott P.; Lin, Yuehe; et al. (Carbon energy, 2023)
The keen interest in fuel cells and metal‐air batteries stimulates a great deal of research on the development of a cost‐efficient and high‐performance catalyst as an alternative to traditional Pt to boost the sluggish oxygen reduction reaction (ORR) at the cathode. Herein, we report a facile and scalable strategy for the large‐scale preparation of a free‐standing and flexible porous atomically dispersed Fe–N‐doped carbon microtube (FeSAC/PCMT) sponge. Benefiting from its unique structure that greatly facilitates the catalytic kinetics, mass transport, and electron transfer, our FeSAC/PCMT electrode exhibits excellent performance with an ORR potential of 0.942 V at −3 mA cm−2. When the FeSAC/PCMT sponge was directly used as an oxygen electrode for liquid‐state and flexible solid‐state zinc‐air batteries, high peak power densities of 183.1 and 58.0 mW cm−2 were respectively achieved, better than its powdery counterpart and commercial Pt/C catalyst. Experimental and theoretical investigation results demonstrate that such ultrahigh ORR performance can be attributed to atomically dispersed Fe–N5 species in FeSAC/PCMT. This study presents a cost‐effective and scalable strategy for the fabrication of highly efficient and flexible oxygen electrodes, provides a significant new insight into the catalytic mechanisms, and helps to realize significant advances in energy devices. A metal–organic framework‐graft‐derived approach is proposed for bulk preparation of free‐standing and flexible porous atomically dispersed Fe–N‐doped carbon microtube films. Theoretical calculation and experimental results demonstrate that this ultrahigh‐performance film catalyst benefits from the cross‐wrapped carbon microtube network structure that ensures fast electron transfer capability, shortens mass transport pathways, and enhances the utilization of high‐activity Fe–N5 sites for oxygen reduction.